Effect of the fermentation temperature on the degradation of phytic acid in whole-wheat sourdough bread - Yildirim, Rusen Metin; Arici, Muhammet (ELSEVIER, 2019)
Whole-wheat bread is commonly consumed all over the world, in part because of its high nutritional content. These breads have high levels of phytic acid, which can chelate divalent minerals. In this study, lactic acid bacteria (LAB) were isolated from sourdoughs to screen for extracellular phytase activity and to determine the strains showing the highest activity for use in sourdough preparation. Phytase-active LAB strains were identified by 16S rRNA sequencing. The highest extracellular phytase activities were determined to be 803.95 U/mL and 797.88 U/mL, observed with Lactobacilinc brevis HEB33 and Lactobacillus plantarum ELB78, respectively. Sourdough fermentation was performed at 25, 30 and 35 degrees C in order to determine the optimum temperature for the degradation of phytate. To investigate the temperature and strain effects on bread quality parameters, specific volume, texture, color and sensory analyses were performed along with analyses of the phytic acid and mineral contents. The highest phytate degradation was found in sourdough bread prepared with both Lactobacillus brevis HEB33 and Lactobacillus plantarum ELB78 fermented at 25 degrees C. The addition of spontaneously fermented sourdough at all tested temperatures, as well as the fermentation of sourdoughs at 35 degrees C, had negative effects on the quality parameters and sensory evaluation of the bread samples.
Keywords: Sourdough fermentation; Phytic acid; Phytase activity; Lactic acid bacteria; Whole-wheat bread; LACTOBACILLUS-PLANTARUM; FTIR SPECTROSCOPY; BACTERIA; MICROORGANISMS; IDENTIFICATION; HYDROLYSIS; SELECTION; PRODUCTS; CALCIUM; Food Science & Technology